2005
DOI: 10.1576/toag.7.2.089.27065
|View full text |Cite
|
Sign up to set email alerts
|

Post-hysterectomy vaginal vault prolapse

Abstract: Post‐hysterectomy vaginal vault prolapse develops at the time of hysterectomy (vaginal or abdominal) when the superior vaginal support mechanism is disrupted. Understanding the anatomy of vaginal supports and the pathology of post‐hysterectomy vaginal vault prolapse is essential to treating this condition effectively. Treatment should aim at restoring the anatomy and the functions of the vagina. Different treatment alternatives have been described. They are all effective, although some more so than others. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It is not suggested that the anterior vaginal wall be treated in isolation, but rather as part of a continuum from apical to posterior wall defects. Both of these defects have been reviewed recently within The Obstetrician & Gynaecologist and we would like to draw attention to Afifi and Sayed's review of post‐hysterectomy vaginal vault prolapse 64 . Urinary dysfunction should also be considered in planning concomitant surgery.…”
Section: Resultsmentioning
confidence: 99%
“…It is not suggested that the anterior vaginal wall be treated in isolation, but rather as part of a continuum from apical to posterior wall defects. Both of these defects have been reviewed recently within The Obstetrician & Gynaecologist and we would like to draw attention to Afifi and Sayed's review of post‐hysterectomy vaginal vault prolapse 64 . Urinary dysfunction should also be considered in planning concomitant surgery.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of rectocele was found to be significantly lower in SSLF (5%) than in USLS (18%), according to an RCT 5 . A possible explanation is that after the correction of prolapse by SSLF, the vagina deviates to a more dorsal axis 25 . Thus, the anterior compartment becomes the main pressure‐bearing part compared with the posterior compartment.…”
Section: Discussionmentioning
confidence: 98%
“…McCall culdoplasty and sacrospinous fixation can be carried out at vaginal hysterectomy [2]. Suturing the cardinal and uterosacral ligaments to the vaginal cuff at the time of abdominal or laparoscopic hysterectomy is effective in preventing post-hysterectomy vaginal prolapse [3]. …”
Section: Introductionmentioning
confidence: 99%